Critical and historical essays. - Macaulay, Thomas Babington Macaulay, Baron, 1800-1859 (Electric Book Co., 2001)
The second volume of Macaulay's famous essays, including Machiavelli, Francis Bacon, John Bunyan, Madame D'Arblay, Samuel Johnson, and Moore's Life of Lord Byron among others.